Strategies for the Diagnosis of Granulocytic Anaplasmosis in Two Naturally Infected Dogs - Martinescu, Gabriela-Victoria; Ivănescu, Larisa; Ștefănescu, Raluca; Andronic, Lavinia; Mătiuț, Simona; Mîndru, Raluca; Solcan, Gheorghe; Miron, Liviu (Animals (Basel), 2023)
This study describes granulocytic anaplasmosis in two dogs naturally infected with Anaplasma phagocytophilum. The 3-year-old dogs (male and female) came from the same household and were referred to the Faculty of Veterinary Medicine in Iasi for blood donation. They were subject to standard routine tests: haematology blood test, blood smear, and serological tests (VETSCAN® FLEX4 and IDEXX SNAP 4Dx Plus). The female dog had no medical problems, while the male dog experienced joint pain. The blood smear was negative for tick-borne pathogens, and the haematology findings indicated thrombocytopenia in both dogs, with the male dog also displaying eosinophilia. The two dogs were mildly positive in the ELISA tests for the detection of Anaplasma spp. antibodies; therefore, the blood samples were tested using the qRT-PCR method for Anaplasma platys and Anaplasma phagocytophilum. The qRT-PCR result was negative for A. platys, but it was positive for A. phagocytophilum. The treatment consisted of the administration of doxycycline for 28 days. In conclusion, the high number of cases with non-specific clinical signs, the different sensitivity and specificity of the immunochromatographic serological tests, as well as the possibility of confusing the morula during the cytological examination, make the molecular test mandatory for precise diagnosis.